Analisis Implementasi dan Keberlanjutan Bisnis BagoMix di Kota Palembang - gheafany pebrina vinantara; Muhammad Bagus Fachri; Yulizar Kasih (Universitas Multi Data Palembang, 2026)
This study analyzes the implementation and sustainability of BagoMix, an innovative fried meatball dough with chicken and shrimp flavors in Palembang City, featuring variants of wood ear mushrooms, mustard green essence, and oyster mushrooms. The business, which began in June 2025, utilizes online pre-order strategies, offline sales in university canteens, and resellers, with packaging and product innovations based on consumer feedback. A survey of 50 respondents showed high interest (94% strongly liked it), particularly among students aged 20-24 who prioritized taste and a hybrid offline-online sales model. Positive results include increased sales and sustainable prospects through variant innovation and adaptation to the ready-to-cook snack market